Towards an effective merger review policy: A defence of rebuttable structural presumptions - Filippo Maria Lancieri; Tommaso Valleti (University of Chicago Booth School of Business, Stigler Center for the Study of the Economy and the State, 2024)
We discuss the design of an effective merger review policy for the 21st century. We argue that the practice of the past decades is inadequate and propose a move towards much stronger rebuttable structural presumptions. These presumptions establish that all mergers above certain thresholds are illegal unless the merging parties can prove that merger-specific efficiencies will be shared with consumers and yield tangible welfare gains. These presumptions are grounded on solid economics and also acknowledge the real-world limitations in enforcement resources and information asymmetries between companies and regulators. We outline how to establish such presumptions in practice, defending the implementation of an ex-ante system that selects in advance (rather than per transaction) which companies and markets are subject to the presumption. Finally, we outline which merger-related efficiencies can rebut the presumption.
Keywords: 330